2014
DOI: 10.1155/2014/518276
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Control Method of Active and Semiactive Control: New Framework for Vibration Control

Abstract: A new control design framework for vibration control, the cooperative control of active and semiactive control, is proposed in the paper. In the cooperative control, a structural system having both of an actuator and a semiactive control device, for example, MR damper and so forth, is defined as the control object. In the proposed control approach, the higher control performance is aimed by the cooperative control between the active control with the actuator and the semiactive control with the semiactive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For further introduction to the concept of controllability with diverse applications, refer to major contributions [1][2][3][4][5][6][7][8][9][10] and related references therein. The concept of controllability with applications in engineering has been studied by many authors, a part of which can be found in [11][12][13][14][15][16] and in related references therein. Results obtained in this paper can be used in relevant applied studies in engineering, e.g., [17][18][19][20], for derivation of diverse control regimes.…”
Section: Introductionmentioning
confidence: 99%
“…For further introduction to the concept of controllability with diverse applications, refer to major contributions [1][2][3][4][5][6][7][8][9][10] and related references therein. The concept of controllability with applications in engineering has been studied by many authors, a part of which can be found in [11][12][13][14][15][16] and in related references therein. Results obtained in this paper can be used in relevant applied studies in engineering, e.g., [17][18][19][20], for derivation of diverse control regimes.…”
Section: Introductionmentioning
confidence: 99%